Age of Pre-Neoglacial Cirque Moraines in the Central North American Cordillera - Thompson Davis, P.; Osborn, Gerald (Géographie physique et Quaternaire, 1987)
ABSTRACTIn the western mountains of the United States and Canada are pre-Neoglacial cirque moraines that lie up to about 3 km outside Neoglacial moraines. There is considerable uncertainty as to the ages of the outer moraines and whether or not they are age-equivalent from range to range. The variety of assigned radiocarbon ages found in the literature may be partly due to some authors' use of minimum-limiting dates as near-absolute dates, and use of dates that cannot be definitely related to the deposits in question. With one possible exception, all the dated moraines described in the literature could be as old as the type Temple Lake moraine of Wyoming which has a minimum age of about 11,400 yrs BP based on a recently obtained radiocarbon date. Nearly all paleoecological proxy data from the North American Cordillera, generally derived from continuous sedimentary records, suggest that early Holocene climate was warmer than at present. Global circulation models also suggest an early Holocene thermal maximum in the Cordillera, probably due to Milankovitch forcing. For these reasons a proposal gaining popularity in the literature that widespread "Mesoglaciation" occurred in early Holocene time is premature. We hypothesize that most, if not all, of the moraines in question are correlative and date from Late Pleistocene time.